Sistem Informasi Pendaftaran Magang Dinas Pemuda Dan Olahraga Provinsi Sumatera Utara - Samsudin Samsudin; Nurhalizah Nurhalizah; Ulfa Fadilah (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2022)
Abstract In this digital era, almost all human activities involve the internet. Certain agencies and fields want all processes in their offices to be fast and practical, as well as acceptance of internships or practical work. Usually, students who are in their 7th semester are required to take practical work courses or internships. the registration process is not short and time-consuming. Starting from students who apply for internships in the Study Program section, students receive a cover letter for practical work which will be brought to the destination agency. Students will bring a cover letter to the institution they are going to and wait for days or even weeks to find out whether their internship application is accepted or not. This makes students have to go back and forth to check whether the practical job application is accepted or not. This complicated and inefficient application process prompted us to develop an internship registration information system to address this problem. Our research uses the Software Development Life Cycle (SLDC) method or the so-called waterfall model. The system created and developed is websie-based using HTML, MySQL database, PHP programming language and Visual Studio Code as text editor. With this system, it is hoped that it will make it easier for companies or general sub-sectional agencies to notify the practice of accepting internships will be accepted or not. Keywords: Information System, Internship, Waterfall, Website